First in the desert St. Paul the Hermit in text and tradition - Agaiby, Elizabeth (Texts and studies in Eastern Christianity, 2025)
"This volume invites the reader to a journey into the mystery that is St. Paul the First Hermit. Presented in nine language traditions that span ten centuries of transmission, Paul's vitae are a case study in cultural fusion and diversity. Assembled here for the first time, they provide the scaffolding for the volume that offers a window into the world of Eastern Christianity that consists of deeply interconnected, diverse communities. We learn about churches and monasteries and libraries; about books and relics; about art and iconography; and about the place of St. Paul in various liturgical traditions"--